2012
DOI: 10.1210/me.2012-1139
|View full text |Cite
|
Sign up to set email alerts
|

20-HETE Induces Hyperglycemia through the cAMP/PKA-PhK-GP Pathway

Abstract: We previously generated cytochrome P450 4F2 (CYP4F2) transgenic mice and showed high 20-hydroxyeicosatetraenoic acid (20-HETE) production, which resulted in an elevation of blood pressure. However, it was unclear whether 20-HETE affected glucose metabolism. We measured fasting plasma glucose, insulin, hepatic CYP4F2 expression, and 20-HETE production by hepatic microsomes, and hepatic 20-HETE levels in transgenic mice. We also assessed glycogen phosphorylase (GP) activity and the cAMP/protein kinase A (PKA)-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
2
14
1
Order By: Relevance
“…3). The CYP4F2 transgenic mice had elevated levels of 20-HETE, compared with the levels in the controls in the liver (0.55±0.1, vs. 0.17±0.05 ng/mg pro) and the kidney (0.70±0.13, vs. 0.37±0.14 ng/mg pro), as previously reported (15). The total DiHETE levels were markedly higher in the liver (7.92±1.71, vs. 2.74±0.6 ng/mg pro) and kidney (1.32±0.24, vs. 0.64±0.13 ng/mg pro) of the transgenic mice, compared with the wild-type control mice.…”
Section: Eicosanoid Quantification Using Lc-ms/ms Analysissupporting
confidence: 86%
“…3). The CYP4F2 transgenic mice had elevated levels of 20-HETE, compared with the levels in the controls in the liver (0.55±0.1, vs. 0.17±0.05 ng/mg pro) and the kidney (0.70±0.13, vs. 0.37±0.14 ng/mg pro), as previously reported (15). The total DiHETE levels were markedly higher in the liver (7.92±1.71, vs. 2.74±0.6 ng/mg pro) and kidney (1.32±0.24, vs. 0.64±0.13 ng/mg pro) of the transgenic mice, compared with the wild-type control mice.…”
Section: Eicosanoid Quantification Using Lc-ms/ms Analysissupporting
confidence: 86%
“…In addition to the vascular system, Nowicki et al have reported that 20-HETE inhibited a cAMP-dependent pathway in the kidney of rats that consumed a potassium-deficient diet (33). By contrast, results from our previous study demonstrated that 20-HETE activated the cAMP pathway in the liver of CYP4F2 transgenic mice (34). In blood pressure regulation, 20-HETE exhibited both prohypertensive and antihypertensive actions through vasoconstriction and natriuresis.…”
Section: Disccusioncontrasting
confidence: 54%
“…In addition to the formation of PGs, terminal hydroxylation of AA yields the potent vasoconstrictive and proinflammatory eicosanoid 20-HETE (25). 20-HETE can induce hyperglycemia through the cAMP/ PKA-PhK-GP pathway (39), and 20-HETE levels have been positively associated with liver cirrhosis (40). We found that the hepatic 20-HETE level was significantly reduced in CD36Tg mice, but it was restored to the WT level upon Dox treatment (Fig.…”
Section: Creation Of Cd36tg Mice That Overexpress Cd36 In the Livermentioning
confidence: 73%
“…In addition to the reduction of PGs, we showed that the hepatic level of 20-HETE was also decreased in the CD36Tg mice without affecting the level of the parent arachidonic acid. The decreased formation of 20-HETE may have also contributed to the overall improvement of metabolic function, because this arachidonic acid metabolite has been shown to induce hyperglycemia (39).…”
Section: Discussionmentioning
confidence: 99%